2005
DOI: 10.1196/annals.1352.015
|View full text |Cite
|
Sign up to set email alerts
|

Punica granatum (Pomegranate) Juice Provides an HIV‐1 Entry Inhibitor and Candidate Topical Microbicide

Abstract: Background: For ≈ 24 years the AIDS pandemic has claimed ≈ 30 million lives, causing ≈ 14,000 new HIV-1 infections daily worldwide in 2003. About 80% of infections occur by heterosexual transmission. In the absence of vaccines, topical microbicides, expected to block virus transmission, offer hope for controlling the pandemic. Antiretroviral chemotherapeutics have decreased AIDS mortality in industrialized countries, but only minimally in developing countries. To prevent an analogous dichotomy, microbicides sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 85 publications
0
32
0
1
Order By: Relevance
“…The pomegranate has been used in phage amplification assays as a viricidal agent (De Siqueira and others 2006). In addition, pomegranate extract has been reported to have microbiocidal effects on HIV‐1 (Neurath and others 2005).…”
Section: Other Propertiesmentioning
confidence: 99%
“…The pomegranate has been used in phage amplification assays as a viricidal agent (De Siqueira and others 2006). In addition, pomegranate extract has been reported to have microbiocidal effects on HIV‐1 (Neurath and others 2005).…”
Section: Other Propertiesmentioning
confidence: 99%
“…[1][2][3][4] The popularity of pomegranate juice increased significantly in the United States after laboratory and clinical studies suggested that its consumption could decrease the risk of cardiovascular disease, 5 suppresses prostate 6 and breast cancers, 7 and it might even augment the effect of HIV treatment regimens. 8 Pharmacokinetic drug interactions involving citrus products have received considerable attention in the last 15 years. In early studies as far back as 1989, it was demonstrated that grapefruit juice increases the bioavailabilty of the calcium channel antagonists felodipine and nifedipine in humans.…”
mentioning
confidence: 99%
“…A decrease in virucidal activity at ZnSO 4 concentrations 0.29, 0.144 and 0.288 mg mL -1 to punicalagin and 2.88 to PRE may indicate competition for a specific protein and or binding site, hindering potentiation. The virucidal mode of action of pomegranate polyphenols has yet to be elucidated, however other research has shown the interaction between polyphenols with envelope viral glycol proteins of influenza [7, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of α-glucosidase and human leukocyte elastase activity by PRE has been reported [6]—this action was claimed to impede viral attachment and penetration via disruption of the glycosylation of viral glycoproteins. Pomegranate juice extracts have antiviral effects against human immunodeficiency virus (HIV); the mechanism of action appeared to inhibit the binding of the HIV-1 envelope glycoprotein gp 120, preventing the interaction of HIV-1 with the CD4 receptor, and thus reducing the infectivity of the virus [7]. …”
Section: Introductionmentioning
confidence: 99%